A development module of chemistry learning based on chemo-entrepreneurship oriented - Warni Arfin; Latisma Latisma; Budhi Oktavia (International Conferences on Educational, Social Sciences and Technology)
Chemo-entrepreneurship has been used as a contextual learning in chemistry and it can be used to study the material processing into a product of economic value. The aim of this research was to produce teaching material in the form a chemistry module based chemo-entrepreneurship oriented for grade XI students on the odd semester. The research and development approach was used in this study. The data were collected through interviews, observations, and questionnaires. The result of the analysis showed the validation score of the module as very valid. Practicality tests based on student and teacher responses have shown that positive response toward module of chemo-entrepreneurship oriented. The effectiveness test module has been done based on student learning outcomes and showed effective category. In conclusion, the finding showed the module based chemo-entrepreneurship oriented for chemistry learning as valid, practical and effective for use in grade XI students on the odd semester.